Company analysis: SwitchBot / Nurlaila Aseelah Azlee - Azlee, Nurlaila Aseelah (2022)
This is an effort to understand how ideas can be put into practise. Every student at UiTM Arau Cawangan Perlis is required to complete a case study project as part of their studies. As a result, we had the opportunity to study a business called SwitchBot the smart curtain, which is actually headquartered in the United States. The company's general information was gathered in the first section of the project report. Main and secondary sources are both used to collect information. The advanced topic analysis is found in the second section of the article. Objective of the project is to work on the background, organizational structure, products and services that SwitchBot provides. Last but not least, we look at the company's financial successes, both in terms of how they handle their finances and the results of their financial management. Goals describe what a company needs to accomplish. A strategy is a course of action for achieving a set of objectives. Every company must devise a plan for achieving its objectives, which includes a marketing strategy as well as successful management. In this case study, we used SWOT analysis to examine the company's strengths, limitations, opportunities, and risks in the real world.